Adaptive predictive control of a distillation column - Yoon, Tae-Woong; Yang, Dae Ryook; Lee, Kwang Soon; Kwon, Young-Min (Zielona Góra: Uniwersytet Zielonogórski)
Distillation processes reveal complicated multivariable nonlinear dynamics for which it is difficult to design a high-performance control system. This paper proposes an adaptive control scheme for a distillation column. The proposed adaptive system consists of a multi variable receding-horizon predictive controller using a transfer function model and a recursive least-squares (RLS) based estimator. Simulations show a consistent closed-loop performance despite the uncertain nonlinear characteristics of the distillation column.
Keywords: adaptive control; multivariable predictive controller; distillation column